Wood of Trema micrantha (L.) Blume from Veracruz, México - Quintanar-Isaías, Alejandra; Jacobo-Villa, Marco A.; López-Binnqüist, Citlalli; Flores-Hernández, Noé; Jaramillo-Pérez, Ana Teresa; de la Paz Pérez-Olvera, Carmen (Instituto de Ecología, A.C., 2012)
The microscopic anatomy, hydraulic and mechanical indices of the wood of 28 trees of thespecies Trema micrantha of four localities in the municipalities of Xico and Coatepec in Veracruz State,Mexico were studied. In addition, macroscopic characteristics such as relative density and moisturecontent were determined. Results showed that T. micrantha has a mesomorphic xylem characterizedby low resistance to cavitation, low values of relative density, low indices for vessel and fiber collapseand a high index of vulnerability. An analysis of variance shows that of all the characteristics studied,only the rate of collapse of the vessels is similar between individuals and populations. Multiple comparisontests show that wall thickness and the number of rays separate populations Bola de Oro andBarrales from the other sites of study.Carpentry tests reveal that wood from T. micrantha is resistant tosplitting when nailed, is well suited to assemblage, and thus, it is recommended for use in carpentry inrural areas.